-4-43x=7x-6

Simple and best practice solution for -4-43x=7x-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4-43x=7x-6 equation:


Simplifying
-4 + -43x = 7x + -6

Reorder the terms:
-4 + -43x = -6 + 7x

Solving
-4 + -43x = -6 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-4 + -43x + -7x = -6 + 7x + -7x

Combine like terms: -43x + -7x = -50x
-4 + -50x = -6 + 7x + -7x

Combine like terms: 7x + -7x = 0
-4 + -50x = -6 + 0
-4 + -50x = -6

Add '4' to each side of the equation.
-4 + 4 + -50x = -6 + 4

Combine like terms: -4 + 4 = 0
0 + -50x = -6 + 4
-50x = -6 + 4

Combine like terms: -6 + 4 = -2
-50x = -2

Divide each side by '-50'.
x = 0.04

Simplifying
x = 0.04

See similar equations:

| 2(x-3)+5x=9x-14 | | 4(x-3)-3=-27 | | 10+5y=50 | | x^2+4q-45=0 | | t^2+3t-6=0 | | 3(-2x+1)-2(x+13)=7x-4(1-x) | | 2(3m-1)=16 | | 5(b+2)=30 | | 2x+6x=-8+7x | | 4y+3=21 | | 9(-4)-(-2)= | | 9x+9=7-(5x-6) | | -4(6x-7)+8(9x+7)=2 | | 11x^2-7x-10=0 | | -3(w-9)+8w+1= | | -8(x-7)+2(2x+5)=10 | | (5x-3)=(14-48) | | 6(5+c)=5c-4 | | x(x-6)=391 | | 7x-1=4x-8(7+x) | | 0.16x+0.1y=0.08 | | 5x(12x-7)-4x(15x-11)=30+29x | | 30x=100+20x | | 3y+6x=36 | | 0.03x+0.09y=-0.27 | | 3(2f+4)=2(3-6) | | 3(5x+3)=36+6x | | -3x^2+7x+6=f(x) | | (x^3-27)(x^3-27)(x^3-27)=0 | | 5x(12x-7)-4x(15x-11)=30-29x | | -1/6(24)= | | 2/3(12)= |

Equations solver categories